The Evolution of the Prohibition of Genocide: From Natural Law Enthusiasm to Lackadaisical Judicial Perfunctoriness – And Back Again? - Klaus, Julia (Goettingen Journal of International Law, 2021)
International legal scholarship and practice have reached a point where it is undisputed that the prohibition of genocide has the status of jus cogens and entails erga omnes obligations. It is, however, astonishing how little academic focus has been dedicated to the normative development leading to this extraordinary rank. In a legal regime with as little hierarchical structure as public international law, examining the birth process of such a norm promises considerable insights into normative formation in general and may inform jurisprudential theories on the nature of international law. This article illustrates the evolution of the prohibition of genocide by outlining the way to the 1948 UN Genocide Convention and the later interpretations of the norm. It traces the origin of the genocide prohibition to naturalistic ideas of overarching laws of humanity in international law and follows its development into the early 21st century. An analysis of international jurisprudence reveals that, after the jus cogens status of the prohibition of genocide and its erga omnes dimension had been settled, international judges handled the norm in a surprisingly lackadaisical and perfunctory manner. The very recent ICJ order on provisional measures in the Myanmar Genocide case potentially marks a return towards a deeper focus on moral facts determining the prohibition that point to naturalistic theories persisting, notwithstanding the positivistic mainstream approaches to international law. The article contributes to a more accurate picture of and greater academic interest in these naturalistic undercurrents.<br
Keywords: public international law; international criminal law; history of international law; jurisprudence; legal theory; genocide